STRATEGI PELATIHAN KEWIRAUSAHAAN BERBASIS DIGITAL MARKETING DALAM MEMBANGUN PENGEMBANGAN EKONOMI BAGI PENYANDANG DISABILITAS - Ariprabowo, Tri; Putri, Mananda; Herlambang, Yudha Kusuma; Alana, Moh Aslich (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study explores the potential of digital marketing as a tool for empowering entrepreneurship for people with disabilities in the context of increasing globalization. In today's era of globalization, people with disabilities face various barriers such as poor treatment and limited accessibility, regulations that promote economic mobility must be enforced. The research method uses a literature study to analyze various sources related to digital marketing-based entrepreneurship education in the concept of people with disabilities. The results of the study show that this training not only improves the technical skills of people with disabilities, but also helps them enter the digital market and find more inclusive business opportunities. Examples of practices around the world show that digital marketing training can increase participants' income and self-confidence. Discusses how digital marketing can help overcome the problems faced by people with disabilities. It also discusses ideal training strategies that include technological accessibility, practical learning, and post-training support. According to the conclusion of this study, the use of digital marketing in entrepreneurship training can enable people with disabilities to make significant economic contributions and drive positive economic and social change. Keywords: Digital marketing, people with disabilities, entrepreneurship, training